2019
DOI: 10.1186/s13104-019-4509-4
|View full text |Cite
|
Sign up to set email alerts
|

Re-recruiting postpartum women living with HIV into a follow-up study in Cape Town, South Africa

Abstract: Objective Recruitment and retention present major challenges to longitudinal research in maternal and child health, yet there are few insights into optimal strategies that can be employed in low-resource settings. Following prior participation in a longitudinal study following women living with HIV through pregnancy and breastfeeding in Cape Town, women were re-contacted at least 18 months after the last study contact and were invited to attend an additional follow-up visit. We describe lessons le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…These findings suggest that transfers may become more common as treatment programs expand and patients can find ART centers close to their homes, and that participants in longitudinal studies may require frequent communications to update contact information, particularly in settings where mobility is common. 18 The very few data that we collected with the tracing activity (strongly affected by the COVID pandemic) are in line with that reported above, since several silent transfers were documented and in some cases no information was found at the address given. We cannot exclude that, in this last case, because of the stigma still associated with HIV infection, women may have given a wrong address at the enrolment visit.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings suggest that transfers may become more common as treatment programs expand and patients can find ART centers close to their homes, and that participants in longitudinal studies may require frequent communications to update contact information, particularly in settings where mobility is common. 18 The very few data that we collected with the tracing activity (strongly affected by the COVID pandemic) are in line with that reported above, since several silent transfers were documented and in some cases no information was found at the address given. We cannot exclude that, in this last case, because of the stigma still associated with HIV infection, women may have given a wrong address at the enrolment visit.…”
Section: Discussionsupporting
confidence: 83%
“…However, in our study, independent predictive factors for a lack of EID were not clearly identified. Other studies have investigated on this topic: lack of maternal ART or infant prophylaxis, [17][18][19] lack of maternal ANC attendance, 20,21 new maternal HIV diagnosis, 18 lack of information about the importance of early testing 22 have all been identified as possible predictors of the lack of an EID. In one study in rural Malawi (2013-2016) it was also shown that receiving an infant HIV test result was associated to a reduced infant study retention, especially an infant's positive result.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis only included women enrolled in the LACE study, and the patterns and impact of mother–child separation may be different among those not enrolled. The differences in the characteristics of the women enrolled and those not enrolled in LACE have been described in our work elsewhere [37]. Patterns of separation observed in this cohort may differ in other populations, and thus, the observed effects of separation on maternal and child outcomes need to be assessed in other settings.…”
Section: Limitationsmentioning
confidence: 91%
“…The LACE study was designed as a single additional study measurement visit at 36–60 months post‐partum, about 16 months after the last MCH‐ART study visit, to evaluate longer‐term maternal HIV treatment outcomes and child health. Details of recruitment into the LACE study are described elsewhere [37]. Of the 471 mothers who enrolled in MCH‐ART, 353 (75%) consented and enrolled in the LACE study.…”
Section: Methodsmentioning
confidence: 99%
“…However, many potential participants lack telephones or may use caller ID to block unsolicited calls resulting in lower response rates and/or nonresponse bias (14). Electronic means of contacting potential participants, including text message and email, is increasing (15). While text messages and emails are effective in recruiting and reducing loss to follow-up, they can be used in a wide range of settings (16,17).…”
Section: Introductionmentioning
confidence: 99%